Molecular Analysis of the Glutathione S-Transferase System in Patients with Depression - Anjos, Laura Raniere Borges dos; Silveira, Luciana Carvalho; da Silva Santos, Rodrigo; Machado, Victor Hugo; Reis, Angela Adamski da Silva (Multi-Science Journal, 2018)
Depression is defined as a mood disorder in which changes in temperament occur making the patient sad, lacking energy and, at a severe stage, with suicidal thoughts. Depression is a multifactorial tantrum that may be associated with changes in neurotransmitters, social or genetic factors. It is suggested that oxidative stress may be associated with worsening of depression in patients not treated with antidepressants. In addition, it is known that oxidative stress is favored in situations where the individual presents a compromise in the function of antioxidant enzymes, such as GSTP1. The objective of the present study was to verify if the GSTP1 gene polymorphism confers genetic susceptibility to depression. Methods: PCR-RFLP technique was used to analyze polymorphisms. The samples were collected at the Brain Institute Clinic were divided into two groups, case and control, for later study of the heterozygous genotypes (Ile / Val), wild homozygote (Ile / Ile) and mutant homozygote (Val / Val). The results suggest that there was no statistically significant correlation between GSTP1 polymorphism and the risk of developing depression (p = 0.1835). Conclusions: In this sense, more studies should be carried out in search of more consistent results, thus allowing more accurate correlation regarding the role of this polymorphism with the susceptibility to depression.